Flexibilização da jornada de trabalho dos servidores técnicos administrativos em educação no Instituto Federal de Educação, Ciência, e Tecnologia do sudeste de Minas Gerais - Carvalho, Joseli Marcos (2018)
The flexibilization of the working hours of the administrative education employees (AEEs) has been discussed within the Federal Education Institutions (FEI). Given its repercussions, a case study is proposed at the Federal Institute of Education, Science, and Technology of Southeastern Minas Gerais, Brazil, with the objective of verifying how the many actors of the Federal Institute interpret and evaluate the working hours flexibilization process (WHF) of AEEs, in the form of its reduction. A case study was conducted through semi-structured interviews, verifying the literature on the subject, and documental analysis of the flexibilization process. Many actors of the FEI partook of the research, which allowed a wide perspective at the process studied and a better understanding of the process and the factors surrounding it. For the data analysis, a qualitative approach was used through content analysis. The legislation regarding the WHF was found to be unclear concerning the flexibilization in Brazilian public administration. Most norms and regulations adopted by FEIs in Brazil do not define clear criteria for granting working hours to AEE. The national unions (FASUBRA and SINASEFE) seek the application of the WHF according to Decree n. 1590/1995, and fight for the reduction of the working hours (RWH) to 30 hours per week for all AEEs. The WHF of AEEs in the Federal Institute Southeast MG arose from a demand from the AEEs who actively participated in the entire process. The FI Southeast MG campi differ from each other, which makes it difficult to standardize the WHF within the institution. The Federal Institution extended the hours of service to users and contributed to aspects related to health, work, leisure (family), and study (training) of AEEs. The study on the WHF for AEEs of the FI Southeast MG contributes to the discussion on the subject since there are few studies in this area. It was important to study the process of FWH for AEEs of IF Southeast MG, with a wide perspective at the process, providing information that can support decisions and discussions on the subject.